Interplay of Risk Management in the Multi-Disruption Era and Agency Theory Insights: A Literature Review - Afifawati, Nisrina; Khasanah, Lia; Giovanni, Axel (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research aims to provide empirical insights into the intersection of risk management and agency theory, focusing on their role in preparing for and navigating contemporary disruptions. Risk management is conceptualized as a structured approach for addressing uncertainty related to threats, involving risk assessment, strategy formulation, and risk mitigation through empowerment and resource management. Using a literature review methodology, the study unveils a substantial influence of risk management on entrepreneurial Enterprise Risk Management (ERM), particularly within the domain of intellectual capital. The findings deepen our understanding of how effective risk management practices are crucial in navigating the dynamic landscape of modern business disruptions.